The Effect of Quality of Work Life on Generation Y Employee Engagement Through Job Satisfaction as a Mediator Variable at PT.C - Novitasari, Aulia (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
—Employee Engagement is one aspect of the company's success to achieve the company's goalsoptimally. This study aims to analyze the effect of Quality of Work Life on Employee Engagement ofGeneration Y employees with Job Satisfaction as a mediator variable at PT.C. This study uses theStructural Equation Model – Partial Least Square (SEM-PLS) method. This research was conducted atPT.C with a sample of seventy-seven respondents. The results of this study indicate that Quality of Work-Life has a positive and significant effect on employee Engagement, Quality of Work Life has a positive andsignificant effect on Job Satisfaction, Job Satisfaction has a positive and significant effect on EmployeeEngagement, there is an indirect effect between Quality of Work Life on Employees Engagement throughjob satisfaction positively and significantly.